2012
DOI: 10.1111/j.1365-2702.2011.03995.x
|View full text |Cite
|
Sign up to set email alerts
|

Job conditions, job satisfaction, somatic complaints and burnout among East African nurses

Abstract: Aims.  To describe job conditions, job satisfaction, somatic complaints and burnout of female East African nurses working in public and private hospitals and to determine how these well‐being outcomes are associated with job conditions. Background.  Insight into job conditions, health and well‐being status and their interrelation is virtually lacking for East African nurses. Design.  Cross‐sectional survey of 309 female nurses in private and public hospitals in Kenya, Tanzania and Uganda. Methods.  Nurses comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 37 publications
6
91
1
7
Order By: Relevance
“…The other three were motivation factors: autonomy of practice, work worth to self and others and professional role enactment. The nurses were most satisfied with work worth to self and others, supporting findings by Doef et al [17] who found that nurses in East Africa feel more accomplished. South African nurses were found to be moderately accomplished Gaki et al [22] The findings from South Africa can be compared with those in Kenya since there are cultural similarities between the two countries.…”
Section: Subscales Correlationssupporting
confidence: 75%
See 1 more Smart Citation
“…The other three were motivation factors: autonomy of practice, work worth to self and others and professional role enactment. The nurses were most satisfied with work worth to self and others, supporting findings by Doef et al [17] who found that nurses in East Africa feel more accomplished. South African nurses were found to be moderately accomplished Gaki et al [22] The findings from South Africa can be compared with those in Kenya since there are cultural similarities between the two countries.…”
Section: Subscales Correlationssupporting
confidence: 75%
“…This adds to an increasing body of knowledge where for example, Choi et al [1] in Hong Kong also expressed that the factors that attract people to nursing include interesting and challenging work and the ability to help others. Similarly, Doef et al [17] highlighted that providing comfort for patients and the knowing that patients are provided with adequate care were linked to increased job satisfaction. The findings are the same despite cultural differences in the study settings.…”
Section: Satisfaction With Individual Itemsmentioning
confidence: 99%
“…La diferencia entre los que laboran en el área de atención hospitalaria, frente a los que trabajan en un área diferente, se explica por las características propias del trabajo hospitalario de enfermería: una mayor carga laboral (número de pacientes y tiempo de trabajo) (19,24,(26)(27)(28) , carga emocional (exposición al dolor, la muerte) junto con la responsabilidad sobre el bienestar del paciente (5,19) y la rutina diaria (18,19) . La menor prevalencia del síndrome en enfermeros que laboran en áreas no hospitalarias, también fue encontrada en un estudio realizado en Suiza, donde asocian este hallazgo a la autonomía laboral que se presenta en esta área (29) .…”
Section: Discussionunclassified
“…Efforts and investments should be made to improve the job conditions of nurses, as they are key persons in the delivery of health care. 4 Patient satisfaction levels are lower in hospitals with more nurses who are dissatisfied or burned out-a finding that signals problems with quality of care. Improving nurses' working conditions may improve both nurses' and patients' satisfaction as well as the quality of care.…”
Section: Issn: 2320-5407mentioning
confidence: 99%